Building resilient school organizations through transformational leadership - Egerău, Anca Manuela (Technium Social Sciences Journal, 2025)
In an increasingly complex and unpredictable educational landscape, building resilient school organizations is essential for sustainable success. This paper explores the pivotal role of transformational leadership in fostering organizational resilience within educational institutions. Transformational leadership, characterized by vision, inspiration, and a commitment to growth, empowers school leaders to navigate challenges, inspire their teams, and maintain organizational stability during periods of change. Through a comprehensive review of existing literature and case studies, this study identifies key leadership strategies that promote resilience, including fostering a shared vision, encouraging innovation, and cultivating a supportive community. The findings suggest that transformational leaders play a critical role in building adaptive capacities and sustaining positive outcomes even amidst adversity. By integrating transformational leadership principles into school management practices, educational leaders can enhance their organizations' resilience, thereby ensuring long-term effectiveness and growth.